Single-Walled Carbon Nanohorns as Promising Nanotube-Derived Delivery Systems to Treat Cancer - Alazne Moreno-Lanceta; Mireia Medrano-Bosch; Pedro Melgar-Lesmes (MDPI AG, 2020)
Cancer has become one of the most prevalent diseases worldwide, with increasing incidence in recent years. Current pharmacological strategies are not tissue-specific therapies, which hampers their efficacy and results in toxicity in healthy organs. Carbon-based nanomaterials have emerged as promising nanoplatforms for the development of targeted delivery systems to treat diseased cells. Single-walled carbon nanohorns (SWCNH) are graphene-based horn-shaped nanostructure aggregates with a multitude of versatile features to be considered as suitable nanosystems for targeted drug delivery. They can be easily synthetized and functionalized to acquire the desired physicochemical characteristics, and no toxicological effects have been reported in vivo followed by their administration. This review focuses on the use of SWCNH as drug delivery systems for cancer therapy. Their main applications include their capacity to act as anticancer agents, their use as drug delivery systems for chemotherapeutics, photothermal and photodynamic therapy, gene therapy, and immunosensing. The structure, synthesis, and covalent and non-covalent functionalization of these nanoparticles is also discussed. Although SWCNH are in early preclinical research yet, these nanotube-derived nanostructures demonstrate an interesting versatility pointing them out as promising forthcoming drug delivery systems to target and treat cancer cells.